Results of systemic treatment of cutaneous melanoma in inoperable stage III and IV - Cybulska-Stopa, Bożena; Skoczek, Marta; Ziobro, Marek; Świtaj, Tomasz; Falkowski, Sławomir; Morysiński, Tadeusz; Hetnał, Marcin; Cedrych, Ida; Rutkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: The incidence of melanoma is increasing rapidly worldwide. Metastatic melanoma is still an incurable disease, although an era of new drugs is approaching. Current methods to predict outcomes in patients with advanced, metastatic melanoma are limited. A retrospective analysis of a contemporary large group of advanced melanomas was performed to determine clinical prognostic factors that accurately predict survival in patients with metastatic melanoma before the era of new targeted/immunological therapy. Material and methods : The retrospective analysis of 427 patients with metastatic melanoma treated between 1995 and 2005 at two reference oncological centres. Results : The median overall survival time (OS) was 7.1 months (95% CI: 6.7–7.9) and the 1-year, 2-year and 5-year survival rates were 32.3%; 12.5%; 3.9%, respectively. The median progression-free survival time (PFS) after the first line of treatment was 3.5 months (95% CI: 3.1–3.8). There were 19.1% objective responses (CR – 6.1%, PR – 13.0%) and SD – 45.5% after the first line of therapy. The most common adverse events were anaemia, neutropenia, thrombocytopenia, nausea and vomiting. In multivariate analyses: PS (performance status) 0–1, normal serum levels of lactate dehydrogenase (LDH) and aspartate transaminase (AspAT), older age in women, palliative surgical treatment and palliative radiotherapy, type of the first line of therapy (DTIC), and metastatic melanoma of unknown primary site were independent positive predictors for survival. Conclusions : The survival rate of patients with metastatic melanoma has not changed significantly over the last years. We identified a set of independent positive predictors for OS treated with systemic therapy. DTIC still may be useful in treatment of patients in a good general condition and with normal serum levels of LDH. Because the results of treatment of metastatic melanoma are still not satisfactory, the majority of patients should be treated within prospective, randomized clinical trials.